STUDENTS’ PERCEPTION ON THE USE OF ESTAFET WRITING GAME AND PICTURE BASED-CREATIVE WRITING TO NURTURE LOVE OF WRITING - Erna Intanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
To create a quality education, mainly on EFL instruction, the EFL teachers need to be empowered with improving their teaching quality. The students, on the other hand, should also be actively engaged during the instructional activities. Due to the fact that love of “writing” as one of the language skills is not yet established among the EFL university students, the effort of finding out an innovative way of helping them to establish love of creative writing is a must. One of the ways is collaborative writing through Estafet Writing Game and Picture-Based-Creative Writing strategies. Thus, this article aims at describing the students’ voices on the use of those strategies to establish love of creative writing. The study conducted through a reflective questionnaire survey to 165 EFL university students reveals that most of the respondents prefer Estafet Writing Game to Picture-Based Creative Writing in terms of its effectiveness to build their creativity and spontaneity of writing skills. To sum up, these strategies are pedagogically meaningful to improve the EFL students’ creative writing, because they can collaborate with their peers and promote their cooperative communication. Therefore, it is useful to establish love of writing and to stimulate their ideas for writing.